Comparative photo electro catalytic oxidation of real pharmaceutical wastewater using Ag/TiO2: Process optimization and acute toxicity removal - Ates, Ayse Elif; Ates, Sinan; Aydin, Serdar; Varank, Gamze (ELSEVIER, 2025)
Pharmaceutical wastewater contains persistent organic pollutants and bioactive compounds that pose significant environmental risks. Despite extensive studies on photocatalytic degradation, research on real pharmaceutical wastewater remains limited. This study evaluates the performance of silver-doped titanium dioxide (Ag/TiO2) in real pharmaceutical wastewater treatment through photo electro catalytic oxidation (PECO) and electro catalytic oxidation (ECO), with a focus on process optimization, pollutant removal efficiency, and ecotoxicological impacts, and the comparative performance of Ag/TiO2 as both anode and cathode materials. A Central Composite Design (CCD) approach was employed to systematically analyze the effects of pH, reaction time, current density, and temperature on chemical oxygen demand (COD) and UV254 removal efficiencies. Response Surface Methodology (RSM)-based correlation models accurately predicted Results with 98 % reliability. Under optimized conditions, PECO demonstrated its high efficiency in wastewater treatment by achieving 76 % COD and 86 % UV254 removal. Unlike similar studies in literature, which often ignore the synergistic effects of resistant pollutants, this study provides a comprehensive and realistic ecotoxicological assessment. Acute toxicity tests using Daphnia magna revealed that untreated wastewater caused 97 % immobilization, while PECO reduced it to 23 % without dilution in 30 min, highlighting its superior detoxification potential.
Keywords: Photo electro catalysis; Real pharmaceutical wastewater; Ecotoxicity; Process optimization; Ag/TiO2; ULTRASOUND-ASSISTED EXTRACTION; PHOTOCATALYTIC DEGRADATION; DOPED TIO2; ORGANIC POLLUTANTS; MESOPOROUS TIO2; DYES; UV; Engineering; Water Resources